Enforcing club seat contracts in professional sports - Reese, James (SAGE Knowledge. Cases., 2014)
A professional sport team began play in a new stadium. Although the old facility had no such seat inventory, one of the features at the new facility was the addition of 8,800 club seats. According to the marketing materials provided by the team, the new club-seat inventory offers amenities not available at the old stadium, including upscale concessions, a heated and air-conditioned lounge, padded seats, and increased restroom capacity. After the opening of the new stadium, fans complained about their club seat experience, including long concessions and restrooms lines (typically longer than at the old facility) and consistent premium food shortages. In the off-season, the team began the process of sending ticket-renewal invoices for the upcoming season. Approximately 100 club-seat holders declined to renew, claiming the team breached the contract by not providing the services promised. The team attempted to negotiate with the affected customers with limited success.